Treatment mode preferences in rheumatoid arthritis: moving toward shared decision-making - Taylor, PC; Betteridge, N; Brown, T; Woolcott, J; Kivitz, A; Zerbini, C; Whalley, D; Olayinka-Amao, O; Chen, C; Dahl, P; Ponce De Leon, D; Gruben, D; et al. (Dove Medical Press, 2020)
Purpose: Current knowledge of the reasons for patients’ preference for rheumatoid arthritis (RA) treatment modes is limited. This study was designed to identify preferences for four treatment modes, and to obtain in-depth information on the reasons for these preferences. Patients and Methods: In this multi-national, cross-sectional, qualitative study, in-depth interviews were conducted with adult patients with RA in the United States, France, Germany, Italy, Spain, Switzerland, the United Kingdom, and Brazil. Patients’ strength of preference was evaluated using a 100-point allocation task (0– 100; 100=strongest) across four treatment modes: oral, self-injection, clinic-injection, and infusion. Qualitative descriptive analysis methods were used to identify, characterize, and summarize patterns found in the interview data relating to reasons for these preferences. Results: 100 patients were interviewed (female, 75.0%; mean age, 53.9 years; mean 11.6 years since diagnosis). Among the four treatment modes, oral administration was allocated the highest mean (standard deviation) preference points (47.3 [33.1]) and was ranked first choice by the greatest percentage of patients (57.0%), followed by self-injection (29.7 [27.7]; 29.0%), infusion (15.4 [24.6]; 16.0%), and clinic-injection (7.5 [14.1]; 2.0%). Overall, 56.0% of patients had a “strong” first-choice preference (ie, point allocation ≥ 70); most of these patients chose oral (62.5%) vs self-injection (23.2%), infusion (10.7%), or clinic-injection (3.6%). Speed and/or ease of administration were the most commonly reported reasons for patients choosing oral (52.6%) or self-injection (55.2%). The most common reasons for patients not choosing oral or self-injection were not wanting to take another pill (37.2%) and avoiding pain due to needles (46.5%), respectively. Conclusion: These data report factors important to patients regarding preferences for RA treatment modes. Patients may benefit from discussions with their healthcare professionals and/or patient support groups, regarding RA treatment modes, to facilitate shared decision-making.